THE LURE OF THE IMAGE KEBOHONGAN PADA NARASI PEREMPUAN DALAM SYNGUE SABOUR PIERRE DE PATIENCE KARYA ATIQ RAHIMI - Yuli Mahmudah Sentana (POETIKA, 2016)
This study aims to determine the position of the author in women narration. With Rahimi’s background as a feminist, he said that with his novel he voiced the voices of Afghan women. Rahimi offered a strong female figure in the middle of the patriarchal shackles who is able to fight the system. The problem of this study is Rahimi’s ambiguity in narrating women. To determine the position of the author, the research uses the concept of the lure of the image belongs to Lidia Curti. The lure of the image is an offer provided by the author to give positions to women that are in fact not provided by them. Based on the research conducted, the results show that Rahimi keeps women as objects in a patriarchal world. In this case he is not able to pull the women out of the patriarchal zone. The space given to women by Rahimi reinforces male power. What Rahimi written in this novel is the lure of the image according to Curti’s concept which explains it as an image of women given by author or known as female gaze.